Preparation method of patterned copper-plated wave-absorbing honeycomb

Through the preparation method of patterned copper-plated wave-absorbing honeycomb, the problems of high weight gain, low printing accuracy and low design freedom are solved, and the aircraft is lightweight and electromagnetic performance adjustment is achieved, which is suitable for assembly line production.

CN119209029AActive Publication Date: 2024-12-27HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411608518.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-27
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing printing honeycombs have problems such as high weight gain, low printing accuracy, low design freedom and poor electromagnetic adjustment capabilities, which limit their applications in aircraft lightweight and wide-frequency wave absorption.

Method used

By adopting the preparation method of patterned copper-plated wave absorbing honeycomb, the precursor pattern is printed on aramid paper, the node glue is coated and bonded, the copper is plated in the copper plating solution after cutting and stretching, and the phenolic resin is applied. The conductive layer is formed.

Benefits of technology

It realizes a lightweight design with weight gain control within 5%, improves printing accuracy and design freedom, supports electromagnetic performance adjustment of 256-order grayscale, simplifies processing technology and is suitable for assembly line production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119209029A_ABST
    Figure CN119209029A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a patterned copper-plated wave-absorbing honeycomb, and belongs to the field of microwave absorbing materials. The problems that an existing printing honeycomb is high in weight increment, low in printing precision, low in design freedom and poor in electromagnetic adjusting capacity are solved. The method comprises the steps of 1, printing; 2, gluing; 3, overlapping and bonding; 4, cutting and stretching; 5, copper plating; and 6, dipping and curing. The method is used for preparing the patterned copper-plated wave-absorbing honeycomb.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microwave absorbing materials. Background Art

[0002] Aramid honeycomb is a new type of high-performance composite material with the characteristics of light weight, impact resistance, high strength, and aging resistance. It is widely used in advanced equipment such as aircraft. At present, aramid honeycomb continues to develop in the direction of functionalization based on load-bearing. The load-bearing-stealth integrated aramid honeycomb (hereinafter referred to as absorbing honeycomb) can replace the metal skin + absorbing coating structure of traditional aircraft, effectively reducing the weight of the aircraft, improving maneuverability and reducing fuel consumption. According to public literature and patent reports, aramid absorbing honeycombs are mainly composed of the following: ① Impregnated honeycomb: Before the honeycomb is cured and formed, an absorbent is added to the structural resin, usually conductive powder or magnetic powder. The doped resin enables the honeycomb as a whole to absorb radar waves in a specific frequency band; ② Filled honeycomb: Fill the honeycomb pores with absorbent, usually low-density materials such as graphene aerogel; ③ Printed honeycomb: Before the honeycomb is stacked, a conductive layer is printed on the surface of the aramid paper. The inner wall of the honeycomb pores prepared by printing the aramid paper is a three-dimensional frequency selection or metamaterial structure, and the honeycomb as a whole has the ability to absorb waves. The wave absorption capacity of the impregnated honeycomb depends on the amount of absorber added to the resin and the adjustment of its dispersion, and there is a problem of mutual restriction between weight gain and wave absorption performance. The preparation process of aerogel filled with honeycombs is relatively complicated and it is difficult to adjust the wave absorption performance. Compared with the first two types of honeycombs, the main advantages of printed honeycombs are low weight and strong electromagnetic performance adjustment ability. Patent CN117341288 discloses a three-dimensional wave absorption frequency selection material and a manufacturing method thereof, the structure of which is a honeycomb with staggered bonding of aramid paper printed with two-dimensional metamaterial units, and the wave absorption performance of the honeycomb is adjusted by the printed metamaterial structure. The conductive printing material is nano-carbon powder, nano-graphene or various nano-metal powders, and the printed pattern is a circular ring, an elliptical ring, and a regular polygonal pattern. The above invention has achieved certain results in lightweight and broadband wave absorption, but it still has the problems of high weight gain, low printing accuracy, low design freedom, and poor electromagnetic adjustment ability, which limits the application of wave absorbing honeycombs in lightweight and broadband wave absorption. In terms of weight gain, the screen printing layer thickness is usually above 50 microns, with silver coating (density 10.5g / cm 3 ) as an example, the density of 50 micron thick aramid paper is 0.72g / cm 3The weight gain after printing is about 1500%. If calculated based on the 1mm thick printing layer in the above invention, the weight gain per unit area can reach 30000%. In terms of printing accuracy, aramid paper has good wettability to most organic solvents. Therefore, the ink of the traditional screen printing process will smudge on the surface of the aramid paper, greatly reducing the accuracy of the printed pattern. In terms of design freedom, the honeycomb prepared by the above invention is single-sided printed aramid paper, resulting in half of the honeycomb cells having no conductive pattern, limiting the design space of the electromagnetic performance of the honeycomb. In addition, screen printing is a plate printing, and each time the printed pattern is changed, the plate needs to be re-made, and the process is cumbersome. Therefore, how to provide a load-bearing stealth integrated absorbing honeycomb with low weight gain, high printing accuracy and high design freedom to meet the requirements of lightweight and stealth aircraft is the focus and difficulty of current research. Summary of the invention

[0003] The present invention aims to solve the problems of high weight gain, low printing precision, low design freedom and poor electromagnetic regulation capability of existing printed honeycombs, and provides a method for preparing a patterned copper-plated wave-absorbing honeycomb.

[0004] A method for preparing a patterned copper-plated microwave-absorbing honeycomb is carried out according to the following steps:

[0005] 1. Printing:

[0006] Printing precursor patterns on both sides of aramid paper using a metal particle solution to obtain aramid paper covered with the precursor patterns;

[0007] 2. Gluing:

[0008] Coating node glue on the aramid paper covered with the precursor pattern and drying the solvent to obtain the glue-coated aramid paper;

[0009] 3. Overlap bonding:

[0010] The glue-coated aramid paper is stacked and pressed to solidify to obtain stacked and bonded aramid paper;

[0011] 4. Cutting and stretching:

[0012] Cutting the stacked and bonded aramid paper into honeycomb paper stacks and stretching them to obtain a honeycomb structure;

[0013] The precursor pattern is arranged on each surface of the inner wall of the honeycomb cells in the honeycomb structure;

[0014] 5. Copper plating:

[0015] While maintaining the stretched state, immersing the honeycomb structure in a copper plating solution, copper plating for 30 to 120 minutes at a temperature of 30 to 60 degrees Celsius, and finally washing to obtain a honeycomb structure grown by chemical copper plating of the precursor;

[0016] The copper plating solution is composed of agent A, agent B and solvent; the agent A is composed of CuSO4·5H2O, NaOH, sodium potassium tartrate, pH regulator and water; the agent B is HCNO aqueous solution;

[0017] 6. Dipping and curing:

[0018] While maintaining the stretched state, the honeycomb structure grown by chemical copper plating of the precursor is immersed in a phenolic resin containing a diluent, and then taken out and cured to obtain a patterned copper-plated wave-absorbing honeycomb.

[0019] The beneficial effects of the present invention are:

[0020] In response to the demand for lightweight aircraft, the patterned copper-plated honeycomb conductive layer provided by the present invention is only 1 to 2 microns thick, which can control the weight gain within 5% without losing the mechanical properties of the original honeycomb. Compared with other types of absorbing honeycombs that gain dozens of times the weight of the honeycomb itself, the lightweight design of the present invention is significantly ahead.

[0021] In response to the stealth design requirements of aircraft, the copper-plated honeycomb and its preparation method provided by the present invention have high design freedom: first, the precursor pattern is accurately printed on both sides of the aramid paper, the printing accuracy can reach 0.1mm, and it supports the adjustment of grayscale values ​​0 to 255 (i.e. black to white) with a total of 256 grayscale levels. After the node glue position is coated with glue, the accuracy can reach 0.1mm, and then after being immersed in the copper plating solution, the precursor is chemically copper-plated to grow into a copper-plated layer, and the precursors based on different grayscales will cause the grayscale of the copper layer after copper plating to be different; based on this technology, the local electromagnetic performance design and regulation of a single honeycomb cell can be accurately achieved. In addition, the copper-plated honeycomb processing technology is simple and reliable, and can be scaled up to assembly line production, with broad application prospects.

[0022] The invention is used for a method for preparing a patterned copper-plated wave-absorbing honeycomb. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a physical picture of the fully coated patterned copper-plated aramid honeycomb prepared in step six of Example 1;

[0024] Figure 2 This is a schematic diagram of the honeycomb structure of the precursor after chemical copper plating growth in step five of embodiment one;

[0025] Figure 3 This is a schematic diagram of the honeycomb structure of the precursor after chemical copper plating growth in step 5 of Example 2;

[0026] Figure 4 This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step 5 of embodiment 3;

[0027] Figure 5This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step 5 of embodiment 4;

[0028] Figure 6 This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step five of embodiment five;

[0029] Figure 7 This is a precision test chart of printing a precursor pattern in step 1 of Example 3;

[0030] Figure 8 This is a test chart of the accuracy of applying node glue in step 2 of Example 3;

[0031] Fig. 9 are actual pictures of precursor patterns, a is an actual picture of precursor patterns with different grayscales achieved by the printing method of step one of embodiment one, and b is an actual picture of copper patterns deposited on precursor patterns with different grayscales by the chemical copper plating method of step five of embodiment one;

[0032] Fig.10 The surface morphology of the aramid paper covered with the precursor pattern prepared in step 1 of Example 1, a is macroscopic, b is mesoscopic, and c is microscopic;

[0033] Fig.11 The surface morphology of the honeycomb structure after the precursor prepared in step 5 of Example 1 is grown by chemical copper plating, a is macroscopic, b is mesoscopic, and c is microscopic;

[0034] Fig.12 This is the EDS surface analysis of the surface of the aramid paper covered with the precursor pattern prepared in step 1 of Example 1;

[0035] Fig.13 The EDS surface analysis result of the honeycomb structure surface after the precursor prepared in step 5 of Example 1 was grown by chemical copper plating;

[0036] Fig.14 This is a scanning electron microscope micrograph of the copper layer in the honeycomb structure after the precursor prepared in step 5 of Example 1 is grown by chemical copper plating;

[0037] Fig.15 The comparison curves of reflection loss of the geometric gradient 2 prepared in Example 3 and the gray gradient 2 prepared in Example 5 in the X band and the Ku band are shown. DETAILED DESCRIPTION

[0038] Specific implementation method 1: This implementation method is a method for preparing a patterned copper-plated microwave absorbing honeycomb, which is carried out according to the following steps:

[0039] 1. Printing:

[0040] Printing precursor patterns on both sides of aramid paper using a metal particle solution to obtain aramid paper covered with the precursor patterns;

[0041] 2. Gluing:

[0042] Coating node glue on the aramid paper covered with the precursor pattern and drying the solvent to obtain the glue-coated aramid paper;

[0043] 3. Overlap bonding:

[0044] The glue-coated aramid paper is stacked and pressed to solidify to obtain stacked and bonded aramid paper;

[0045] 4. Cutting and stretching:

[0046] Cutting the stacked and bonded aramid paper into honeycomb paper stacks and stretching them to obtain a honeycomb structure;

[0047] The precursor pattern is arranged on each surface of the inner wall of the honeycomb cells in the honeycomb structure;

[0048] 5. Copper plating:

[0049] While maintaining the stretched state, immersing the honeycomb structure in a copper plating solution, copper plating for 30 to 120 minutes at a temperature of 30 to 60 degrees Celsius, and finally washing to obtain a honeycomb structure grown by chemical copper plating of the precursor;

[0050] The copper plating solution is composed of agent A, agent B and solvent; the agent A is composed of CuSO4·5H2O, NaOH, sodium potassium tartrate, pH regulator and water; the agent B is HCNO aqueous solution;

[0051] 6. Dipping and curing:

[0052] While maintaining the stretched state, the honeycomb structure grown by chemical copper plating of the precursor is immersed in a phenolic resin containing a diluent, and then taken out and cured to obtain a patterned copper-plated wave-absorbing honeycomb.

[0053] The beneficial effects of this specific implementation are:

[0054] In response to the demand for lightweight aircraft, the patterned copper-plated honeycomb conductive layer provided in this specific embodiment is only 1 micron to 2 microns thick, which can control the weight gain within 5% without losing the mechanical properties of the original honeycomb. Compared with other types of absorbing honeycombs that gain dozens of times the weight of the honeycomb itself, the lightweight design of this specific embodiment is significantly ahead.

[0055] In response to the stealth design requirements of aircraft, the copper-plated honeycomb and its preparation method provided in this specific embodiment have high design freedom: first, the precursor pattern is accurately printed on both sides of the aramid paper, with a printing accuracy of up to 0.1mm, and supports grayscale values ​​from 0 to 255 (i.e. black to white) with a total of 256 grayscale levels. The node glue position accuracy can reach 0.1mm after dispensing, and then after being immersed in the copper plating solution, the precursor is chemically copper-plated to grow into a copper-plated layer, and the precursors based on different grayscales will result in different grayscales of the copper layer after copper plating; based on this technology, the local electromagnetic performance design and regulation of a single honeycomb cell can be accurately achieved. In addition, the copper-plated honeycomb processing technology is simple and reliable, and can be scaled up to assembly line production, with broad application prospects.

[0056] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the mass percentage of metal particles in the metal particle solution described in step 1 is 30% to 40%; the solvent in the metal particle solution described in step 1 is water, weak acid aqueous solution or organic solvent. Others are the same as specific implementation method 1.

[0057] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the metal particles in the metal particle solution are nano silver particles or nano platinum particles with a particle size of 30nm to 50nm; the weakly acidic aqueous solution is a 10% to 14% HCl aqueous solution by mass; the organic solvent is tri-1,2-propylene glycol monomethyl ether. Other features are the same as specific implementation method one or two.

[0058] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the grayscale form of the precursor pattern in step 1 is the same grayscale, grayscale gradient or grayscale jump. The rest is the same as specific embodiments 1 to 3.

[0059] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the printing described in step 1 is specifically carried out according to the following steps: ① Place the aramid paper in the working area of ​​the printer nozzle, and then use the motion platform to control the printer nozzle to reciprocate on the surface of one side of the aramid paper to print the precursor pattern under the conditions of piezoelectric on-demand ink supply drive, independent drive, nozzle resolution ≥360npi, ink drop volume ≤13pl, emission frequency ≥45kHz, printing width ≥72mm and grayscale of 1dpd~8dpd, and finally dry at room temperature for 30min~60min; ② Repeat step ① to print the precursor pattern on the other side of the aramid paper. The rest is the same as specific implementation methods 12 to 4.

[0060] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the coating method described in step 2 is dispensing, gravure coating or screen printing coating; the drying solvent described in step 2 is specifically dried at a temperature of 50°C to 60°C for 1h to 3h. Others are the same as specific embodiments 1 to 5.

[0061] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that the curing described in step 3 is performed at a temperature of 120° C. to 140° C. for 1 to 3 hours. The rest is the same as Specific embodiments 1 to 6.

[0062] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the area of ​​the precursor pattern described in step 4 accounts for 30% to 100% of the inner wall area of ​​the honeycomb cells; the precursor pattern in the honeycomb structure described in step 4 is a rectangle or an isosceles triangle. Others are the same as specific embodiments 1 to 7.

[0063] Specific implementation nine: This implementation differs from specific implementations one to eight in that: the volume ratio of agent A to agent B in step five is 1:(1.5-3); the volume ratio of agent A to solvent in step five is 1:(2.5-4); the solvent is water; the concentration of CuSO4·5H2O in agent A is 5g / L-8g / L, the concentration of NaOH is 5g / L-8g / L, the concentration of potassium sodium tartrate is 25g / L-30g / L, and the concentration of pH regulator is 3g / L-6g / L; the pH regulator is Na2CO3; the mass percentage of HCHO in agent B is 30%-40%. Others are the same as specific implementations one to eight.

[0064] Specific embodiment 10: This embodiment is different from the specific embodiments 1 to 9 in that: in step 6, the honeycomb structure grown by chemical copper plating of the precursor is immersed in a phenolic resin containing a diluent for 10 to 20 minutes while maintaining the stretched state, then taken out, first cured for 0.5 to 1 hour at a temperature of 70 to 90 degrees Celsius, then cured for 0.5 to 1 hour at a temperature of 110 to 130 degrees Celsius, then cured for 0.5 to 1 hour at a temperature of 140 to 160 degrees Celsius, and finally cured for 1 to 3 hours at a temperature of 170 to 190 degrees Celsius; the mass percentage of the phenolic resin in the phenolic resin containing a diluent is 80% to 95%. The rest is the same as the specific embodiments 1 to 9.

[0065] The following examples are used to verify the beneficial effects of the present invention:

[0066] Embodiment 1:

[0067] A method for preparing a patterned copper-plated microwave-absorbing honeycomb is carried out according to the following steps:

[0068] 1. Printing:

[0069] Printing precursor patterns on both sides of aramid paper using a metal particle solution to obtain aramid paper covered with the precursor patterns;

[0070] The mass percentage of metal particles in the metal particle solution is 40%; the solvent in the metal particle solution is tri-1,2-propylene glycol monomethyl ether;

[0071] The metal particles in the metal particle solution are nano silver particles with an average particle size of 50 nm;

[0072] The grayscale value of the precursor pattern is 120, i.e., light gray;

[0073] 2. Gluing:

[0074] Use a glue dispenser to apply node glue on the aramid paper covered with the precursor pattern, and dry it at a temperature of 60°C for 2 hours to obtain the glue-coated aramid paper;

[0075] 3. Overlap bonding:

[0076] The glue-coated aramid paper is stacked and pressed, and cured at a temperature of 130° C. for 2 hours to obtain stacked and bonded aramid paper;

[0077] 4. Cutting and stretching:

[0078] Cutting the stacked and bonded aramid paper into honeycomb paper stacks and stretching them to obtain a honeycomb structure;

[0079] The precursor pattern is arranged on each surface of the inner wall of the honeycomb cell in the honeycomb structure; the area of ​​the precursor pattern accounts for 100% of the inner wall area of ​​the honeycomb cell; the honeycomb cell in the honeycomb structure is a regular hexagonal cell, the side length of the honeycomb cell is 2.5 mm, and the thickness is 10 mm; the precursor pattern in the honeycomb structure is a rectangle with a size of 2.5 mm×10 mm;

[0080] 5. Copper plating:

[0081] While maintaining the stretched state, immersing the honeycomb structure in a copper plating solution, copper plating is performed for 60 minutes at a temperature of 30° C., the copper plating thickness is about 2 microns, and finally washing is performed to obtain a honeycomb structure grown by chemical copper plating of the precursor;

[0082] The copper plating solution is composed of agent A, agent B and solvent; the agent A is composed of CuSO4·5H2O, NaOH, sodium potassium tartrate, pH regulator and water; the agent B is HCNO aqueous solution; the volume ratio of the agent A: agent B: water is 1:2:3; the concentration of CuSO4·5H2O in the agent A is 5g / L, the concentration of NaOH is 5g / L, the concentration of sodium potassium tartrate is 25g / L, and the concentration of the pH regulator is 3.75g / L; the pH regulator is Na2CO3; the mass percentage of HCHO in the agent B is 34%;

[0083] 6. Dipping and curing:

[0084] Keeping the stretched state, the honeycomb structure grown by chemical copper plating of the precursor is immersed in phenolic resin diluted with acetone for 15 minutes, then taken out, first cured for 0.5 hours at a temperature of 80°C, then cured for 0.5 hours at a temperature of 120°C, then cured for 0.5 hours at a temperature of 150°C, and finally cured for 2 hours at a temperature of 180°C to obtain a fully coated patterned copper-plated aramid honeycomb, abbreviated as full copper plating. The mass percentage of phenolic resin in the phenolic resin diluted with acetone is 95%.

[0085] The aramid paper described in step 1 is of model YT822A and has a thickness of 0.05 mm.

[0086] The printing described in step one is specifically carried out according to the following steps: ① Place the aramid paper in the working area of ​​the printer nozzle, and then use a motion platform to control the printer nozzle to reciprocate on the surface of one side of the aramid paper to print the precursor pattern under the conditions of piezoelectric on-demand ink supply drive, independent drive, nozzle resolution of 360npi, ink drop volume of 13pl, emission frequency of 45kHz, printing width of 72mm and grayscale of 1dpd, and finally dry at room temperature for 30 minutes; ② Repeat step ① to print the precursor pattern on the other side of the aramid paper.

[0087] The node glue described in step 2 is J-71 core strip glue produced by Heilongjiang Petrochemical Research Institute; the width of the glue strip applied with the node glue in step 2 is the side length of the honeycomb cell.

[0088] The phenolic resin described in step six is ​​PR43204 phenolic resin produced by Suzhou Hangyu Composite Materials Co., Ltd.

[0089] Embodiment 2: This embodiment is different from Embodiment 1 in that: the precursor pattern in the honeycomb structure described in step 4 is an isosceles triangle, the base of the isosceles triangle is 2.5 mm, the height is 10 mm, and the width of the isosceles triangle gradually decreases from one side of the honeycomb cell to the other side; and step 6 obtains a geometric gradient patterned copper-plated aramid honeycomb 1, abbreviated as geometric gradient 1. The rest is the same as Embodiment 1.

[0090] The width of the isosceles triangle decreases from the lower side to the upper side of the honeycomb cell, which is the positive direction of the geometric gradient 1. The width of the isosceles triangle decreases from the upper side to the lower side of the honeycomb cell, which is the reverse direction of the geometric gradient 1.

[0091] Embodiment 3: This embodiment is different from Embodiment 1 in that: the honeycomb cells in the honeycomb structure described in step 4 are regular hexagonal cells, the side length of the honeycomb cells is 2.5 mm, and the thickness is 20 mm; the precursor pattern in the honeycomb structure described in step 4 is an isosceles triangle, the base of the isosceles triangle is 2.5 mm, the height is 20 mm, and the width of the isosceles triangle gradually decreases from one side of the honeycomb cell to the other side; step 6 obtains a geometric gradient patterned copper-plated aramid honeycomb 2, abbreviated as geometric gradient 2. The rest is the same as Embodiment 1.

[0092] The width of the isosceles triangle decreases from the lower side to the upper side of the honeycomb cell, which is the positive direction of the geometric gradient 2. The width of the isosceles triangle decreases from the upper side to the lower side of the honeycomb cell, which is the reverse direction of the geometric gradient 2.

[0093] Embodiment 4: This embodiment is different from Embodiment 1 in that: the grayscale form of the precursor pattern described in step 1 is a gradient grayscale, and the grayscale value gradually changes from 120 to 255, that is, from light gray to white; the grayscale of the precursor pattern in the honeycomb structure described in step 4 gradually decreases from one side of the honeycomb cell to the other side; and step 6 obtains a grayscale gradient patterned copper-plated aramid honeycomb 1, abbreviated as grayscale gradient 1. The rest is the same as Embodiment 1.

[0094] The grayscale of the precursor pattern gradually decreases from the bottom to the top of the honeycomb grid as the positive direction of grayscale gradient 1, and the width of the isosceles triangle gradually decreases from the top to the bottom of the honeycomb grid as the reverse direction of grayscale gradient 1.

[0095] Embodiment 5: This embodiment is different from Embodiment 1 in that: the grayscale form of the precursor pattern described in step 1 is a gradient grayscale, and the grayscale value gradually changes from 120 to 255, that is, from light gray to white; the honeycomb cells in the honeycomb structure described in step 4 are regular hexagonal cells, the side length of the honeycomb cells is 2.5 mm, and the thickness is 20 mm; the grayscale of the precursor pattern in the honeycomb structure described in step 4 gradually decreases from one side of the honeycomb cells to the other side; step 6 obtains a grayscale gradient patterned copper-plated aramid honeycomb 2, abbreviated as grayscale gradient 2. The rest is the same as Embodiment 1.

[0096] The grayscale of the precursor pattern gradually decreases from the bottom to the top of the honeycomb grid as the positive direction of the grayscale gradient 2, and the width of the isosceles triangle gradually decreases from the top to the bottom of the honeycomb grid as the reverse direction of the grayscale gradient 2.

[0097] Comparative experiment: The difference between this embodiment and the first embodiment is that the first and fifth steps are eliminated, and an empty cell is obtained in the sixth step. The rest is the same as the first embodiment.

[0098] Table 1:

[0099]

[0100]

[0101] Table 2:

[0102] sample <![CDATA[Average density g / cm 3 > Compare with empty honeycomb weight gain Comparative experiment empty honeycomb 28.0 0% Example 1 Full copper plating 29.3 4.6% Example 2 Geometric Gradient 1 28.7 2.5% Example 3 Geometric Gradient 2 28.9 3.2% Example 4 Grayscale Gradient 1 28.9 3.2% Example 5 Grayscale Gradient 2 28.8 2.9%

[0103] Table 3

[0104] sample Plane compression strength MPa L-axis shear strength MPa W-axis shear strength MPa Comparative test empty honeycomb 1.19 0.87 0.56 Example 1 Full copper plating 1.20 0.84 0.59 Example 4 Grayscale Gradient 1 1.16 0.85 0.57 GJB1874-2021A 0.85 0.61 0.42

[0105] It can be seen from Table 1 that the patterned copper-plated honeycomb prepared in the embodiment has the ability to absorb waves and adjust the absorption frequency band in the range of 1-18 GHz.

[0106] It can be seen from Table 2 that the weight gain of the patterned copper-plated honeycomb prepared in the embodiment can be controlled below 5% compared with the weight gain of the empty honeycomb, and the patterned copper-plated honeycomb prepared in the embodiment is an ultra-light structural and functional integrated composite material.

[0107] It can be seen from Table 3 that the mechanical properties of the patterned copper-plated honeycomb prepared in the embodiment are compared with those of the empty honeycomb and relevant standards. The plane compression strength, L- and W-direction shear strength of the copper-plated honeycomb are the same as those of the empty honeycomb (L and W directions refer to the provisions in the GJB1874-2021A standard), and are higher than the relevant industry standards.

[0108] Figure 1 This is a physical picture of the fully coated patterned copper-plated aramid honeycomb prepared in step six of Example 1; as can be seen from the figure, the copper-plated honeycomb has an orange appearance and a metallic luster.

[0109] Figure 2 This is a schematic diagram of the honeycomb structure of the precursor after chemical copper plating growth in step five of embodiment one; Figure 3 This is a schematic diagram of the honeycomb structure of the precursor after chemical copper plating growth in step 5 of Example 2; Figure 4 This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step 5 of embodiment 3; Figure 5 This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step 5 of embodiment 4; Figure 6 This is a schematic diagram of the honeycomb structure after the precursor is grown by chemical copper plating in step five of embodiment five.

[0110] Figure 7 This is a precision test chart of printing a precursor pattern in step 1 of Example 3; Figure 8 This is a test chart of the accuracy of applying node glue in step 2 of Example 3; Fig. 9 are actual pictures of precursor patterns, a is an actual picture of precursor patterns with different grayscales achieved by the printing method of step one of embodiment one, and b is an actual picture of copper patterns deposited on precursor patterns with different grayscales by the chemical copper plating method of step five of embodiment one; it can be seen from the figure that the printing accuracy can reach 0.1mm, and it supports 256-level grayscale copper plating adjustment, and the node glue dispensing position accuracy can reach 0.1mm.

[0111] Fig.10 This is a surface morphology of the aramid paper covered with a precursor pattern prepared in step 1 of Example 1, a is macroscopic, b is mesoscopic, and c is microscopic; it can be seen from the figure that the nanosilver precursor is evenly distributed on the surface of the aramid paper after printing.

[0112] Fig.11 This is a surface morphology of the honeycomb structure of the precursor prepared in step 5 of Example 1 after chemical copper plating. a is macroscopic, b is mesoscopic, and c is microscopic. After copper plating, a layer of gravel-like copper is deposited and grown on the surface of the precursor.

[0113] Fig.12 This is the EDS surface analysis of the surface of the aramid paper covered with the precursor pattern prepared in step 1 of Example 1; as can be seen from the figure, the precursor component is silver (the gold peak is gold plating for electron microscopy sample preparation).

[0114] Fig.13 This is the EDS surface analysis result of the honeycomb structure surface after chemical copper plating growth of the precursor prepared in step 5 of Example 1; it can be seen from the figure that the chemical deposition layer is copper (the gold peak is gold plating for electron microscopy sample preparation).

[0115] Fig.14 This is a scanning electron microscope micrograph of the copper layer in the honeycomb structure after the precursor prepared in step five of Example 1 is grown by chemical copper plating; as can be seen from the figure, the patterned copper-plated honeycomb conductive layer of Example 1 is only about 2 microns thick.

[0116] Fig.15 The comparison curves of reflection loss of geometric gradient 2 prepared in Example 3 and gray gradient 2 prepared in Example 5 in X-band and Ku-band are shown in the figure. It can be seen from the figure that, under the condition of the same honeycomb degree (20mm) and similar weight gain, the honeycomb plated with gray gradient copper has stronger wave absorption ability than the honeycomb plated with geometric gradient copper, which reflects the advantage of gray gradient printing.

Claims

1. A method for preparing a patterned copper-plated microwave-absorbing honeycomb, characterized in that It is carried out in the following steps:

1. Printing: Printing precursor patterns on both sides of aramid paper using a metal particle solution to obtain aramid paper covered with the precursor patterns; 2. Gluing: Coating node glue on the aramid paper covered with the precursor pattern and drying the solvent to obtain the glue-coated aramid paper; 3. Overlap bonding: The glue-coated aramid paper is stacked and pressed to solidify to obtain stacked and bonded aramid paper; 4. Cutting and stretching: Cutting the stacked and bonded aramid paper into honeycomb paper stacks and stretching them to obtain a honeycomb structure; The precursor pattern is arranged on each surface of the inner wall of the honeycomb cells in the honeycomb structure; 5. Copper plating: While maintaining the stretched state, immersing the honeycomb structure in a copper plating solution, copper plating for 30 to 120 minutes at a temperature of 30 to 60 degrees Celsius, and finally washing to obtain a honeycomb structure grown by chemical copper plating of the precursor; The copper plating solution is composed of agent A, agent B and solvent; the agent A is composed of CuSO4·5H2O, NaOH, sodium potassium tartrate, pH regulator and water; the agent B is HCNO aqueous solution; 6. Dipping and curing: While maintaining the stretched state, the honeycomb structure grown by chemical copper plating of the precursor is immersed in a phenolic resin containing a diluent, and then taken out and cured to obtain a patterned copper-plated wave-absorbing honeycomb.

2. The method for preparing a patterned copper-plated microwave-absorbing honeycomb according to claim 1, characterized in that The mass percentage of metal particles in the metal particle solution described in step one is 30% to 40%; the solvent in the metal particle solution described in step one is water, weakly acidic aqueous solution or organic solvent.

3. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 2, characterized in that The metal particles in the metal particle solution are nano silver particles or nano platinum particles with a particle size of 30nm-50nm; the weakly acidic aqueous solution is a 10%-14% by mass HCl aqueous solution; and the organic solvent is tri-1,2-propylene glycol monomethyl ether.

4. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The grayscale form of the precursor pattern described in step 1 is the same grayscale, grayscale gradient or grayscale jump.

5. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The printing described in step 1 is specifically carried out according to the following steps: ① placing the aramid paper in the working area of ​​the printer nozzle, and then using a motion platform to control the printer nozzle to reciprocate on the surface of one side of the aramid paper to print the precursor pattern under the conditions of piezoelectric on-demand ink supply drive, independent drive, nozzle resolution ≥360npi, ink drop volume ≤13pl, emission frequency ≥45kHz, printing width ≥72mm and grayscale of 1dpd~8dpd, and finally drying at room temperature for 30min~60min; ② Repeat step ① to print the precursor pattern on the other side of the aramid paper.

6. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The coating method described in step 2 is dispensing, gravure coating or screen printing coating; the drying solvent described in step 2 is specifically dried at a temperature of 50° C. to 60° C. for 1 h to 3 h.

7. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The curing described in step 3 is specifically curing at a temperature of 120° C. to 140° C. for 1 h to 3 h.

8. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The area of ​​the precursor pattern described in step 4 accounts for 30% to 100% of the inner wall area of ​​the honeycomb cells; the precursor pattern in the honeycomb structure described in step 4 is a rectangle or an isosceles triangle.

9. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that The volume ratio of agent A to agent B in step five is 1:(1.5-3); the volume ratio of agent A to solvent in step five is 1:(2.5-4); the solvent is water; the concentration of CuSO4·5H2O in agent A is 5g / L-8g / L, the concentration of NaOH is 5g / L-8g / L, the concentration of potassium sodium tartrate is 25g / L-30g / L, and the concentration of pH adjuster is 3g / L-6g / L; the pH adjuster is Na2CO3; the mass percentage of HCHO in agent B is 30%-40%.

10. The method for preparing a patterned copper-plated microwave absorbing honeycomb according to claim 1, characterized in that In step six, while maintaining the stretched state, the honeycomb structure of the precursor after chemical copper plating growth is immersed in a phenolic resin containing a diluent for 10 minutes to 20 minutes, then taken out, first cured at a temperature of 70°C to 90°C for 0.5h to 1h, then cured at a temperature of 110°C to 130°C for 0.5h to 1h, then cured at a temperature of 140°C to 160°C for 0.5h to 1h, and finally cured at a temperature of 170°C to 190°C for 1h to 3h; the mass percentage of phenolic resin in the phenolic resin containing a diluent is 80% to 95%.

Citation Information

Patent Citations

  • Wave-absorbing honeycomb and preparation method thereof

    CN105297530A

  • Axial folding honeycomb structure wave-absorbing composite material and preparation method thereof

    CN113972501A

  • Methods and devices for electromagnetic wave absorption using gradient, coated honeycomb structures

    US20230041555A1

  • KR20240084317A